INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION FOR WATER SERVICE PROVIDERS IN OMAN - Mohammed Said Awadh Salumi; Zaharuzaman Jamaluddin; Norhayah Zulkifli; Omar Durrah (International Journal of Accounting, Finance and Business, 2022)
Water service sector in Oman has various challenges others water shortages, energy-intensive desalination, high residential water consumption, inappropriate groundwater use in agriculture, misdirected subsidies, and a lack of knowledge of integrated water resources management principles by decision makers. Besides, due to a lack of sufficient natural water resources, desalinated sea water is the primary source of tap water in Oman. However, there are also indications that many customers do not trust the government's drinking water and prefer to purchase filled bottles made by commercial water providers. Despite the fact that good quality tap water is available at a lower cost in Oman, the demand for bottled water has increased in recent years due to the salty flavour and bacterial contamination of tap water. As such, the Omani bottled water market is predicted to increase significantly in the next years as a result of rising consumer wellness and healthcare awareness, which has contributed to the market's rise in recent years. This study attempts to examine the influence of service quality and service guarantee on customer satisfaction and consumption using the SERVQUAL model for water service providers in the Sultanate of Oman. Previous discussions and viewpoints demonstrate that adequate consumption models for diverse areas and situations are required to better explain and improve customer consumption.